2008
DOI: 10.1016/j.jim.2008.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative methodologies of regulatory T cell depletion in a murine melanoma model

Abstract: There has been recent interest in the depletion of regulatory T cells (Tregs) as part of a multi-faceted approach to the immunotherapy of melanoma patients. This is in part due recent findings that convincingly show that Tregs are an integral part of regulating and even suppressing an immune response to growing tumor cells. We therefore compared three methods of Treg depletion and/or elimination, utilizing low dose cyclophosphamide (CY), a specific antibody directed against the IL-2 receptor found on Tregs (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
95
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 49 publications
7
95
0
2
Order By: Relevance
“…Recent studies demonstrated that AREG is involved in inflammation. Furthermore, the EGF-like growth factor AREG is expressed by activated Th2 cells, mast cells, eosinophils, and basophils (13)(14)(15)(16). These studies suggest that the function of AREG might be to regulate immune responses.…”
mentioning
confidence: 91%
“…Recent studies demonstrated that AREG is involved in inflammation. Furthermore, the EGF-like growth factor AREG is expressed by activated Th2 cells, mast cells, eosinophils, and basophils (13)(14)(15)(16). These studies suggest that the function of AREG might be to regulate immune responses.…”
mentioning
confidence: 91%
“…Apparently, CD25 depletion temporarily resets the T effector/Treg balance in favor of the T effector subset. In mice several successful methodologies of Treg depletion have been described (20). This led to great interest in the depletion of Tregs as part of a multifaceted immunotherapeutic treatment of melanoma patients.…”
mentioning
confidence: 99%
“…Compared with Ontak, monoclonal antibodies (mAb) against the IL-2R α-chain (CD25) are more effective in reducing Tregs in melanoma-bearing mice (20). In addition, anti-CD25 antibodies had a synergistic effect when combined with dendritic cell-based immunotherapy in mice (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to interfere with the growth of mouse transplantation tumors by PC-61 monotherapy. Usually an effect on tumor growth has been observed only in prophylactic settings when Treg were depleted before or no later than 2 days after tumor inoculation, whereas PC-61-mediated Treg depletion in animals carrying established tumors had generally no or only little effect on tumor growth [25][26][27][28]. Significant therapeutic success was only observed when complex combinatorial approaches were applied such as total body irradiation combined with adoptive T-cell transfer and vaccination [29], and additional treatment with anti-PDL1 antibody [30], but usually mice were treated when tumors were still small (3-4 days after s.c. tumor inoculation).…”
mentioning
confidence: 99%